Linking dissemination and implementation science to Learning Health Systems: Opportunities for Clinical and Translational Science Award institutions. Issue 3 (26th June 2020) - Bennett, Nancy M.; Orlando, Elissa; Meissner, Paul
Abstract: Learning Health Systems (LHS) iteratively implement and evaluate health improvement projects. Dissemination and implementation (D&I) science is the study of evidence-based practices in real-world settings, a critical tool for LHS. This paper explores intersections between LHS and D&I science in Clinical and Translational Science Awards (CTSAs) institutions and identifies critical components of collaboration. We conducted website scans of 34 CTSAs and their home institutions that had Dissemination, Implementation, and Knowledge Translation (DIKT) Workgroup members. We identified linkages between CTSAs and their institutions' LHS. We interviewed six CTSA leaders experienced in LHS and D&I sciences. Nearly half of CTSAs identified an LHS structure on their websites, but only one-third indicates CTSA involvement in these efforts. Interviewees identified key components for successful integration of LHS and D&I sciences: leadership, infrastructure, balance between rigor and efficiency, and aligned incentives. The need for research integration in LHS, to improve evaluation and increase knowledge, is an emerging opportunity for D&I scientists and CTSAs. CTSAs that are engaged in D&I science can introduce and/or expand the role of D&I science in LHS. Collaboration between CTSAs and clinical leaders could result in strengthened relationships between clinical and research enterprises, effective and efficient health care delivery, and improved health.